Absolute quantitation of poly(R)-3-hydroxybutyric acid using spectrofluorometry in recombinant Escherichia coli. Issue 1 (8th August 2018) - Rajankar, Mayooreshwar P; Ravindranathan, Sapna; Rajamohanan, P R; Raghunathan, Anu
Abstract: Poly(R)-3-hydroxybutyric acid (PHB) is a biodegradable natural polymer produced by microorganisms and plants under nitrogen deprivation and physiological stress. Metabolic engineering and synthetic biology approaches are underway to develop strains that can produce PHB and its co-polymers. One of the major limitations to the scaling and success of strain development for biosynthesis of PHB is the absence of fast, accurate, quantitative and scalable methods to estimate PHB in polymer producing cells. In this study, a Nile red-based spectrofluorometric method is developed for absolute quantitation of PHB in recombinant Escherichia coli . The method is a modification of an existing Nile red-based method currently only used for relative quantitation. The two added steps of sonication and ethanol extraction increase the dynamic range of the assay and limit of detection/quantitation. Sonication of PHB standards provides uniform distribution of surface area to volume ratios. This ensures reproducibility and accuracy (lower %relative error) of quantitative staining of granules by Nile red even in a higher dynamic concentration range of 125–1000 µg/ml. Ethanolic extraction of the PHB bound Nile red allows higher recovery and accurate absolute quantitation. To reproduce high recovery and ensure accuracy and precision of the analytical method directly using cells, a protein digestion step was added. This accounted for fluorescence from over-expressed protein and resulted in screening of nonproducers of PHB amongst samples. Thus, the method developed is rapid, accurate, and reproducible, requires low sample volumes and processing compared to other conventional methods. This method is scalable to other PHA's and diverse plastics.